Pengaruh Brand Experience dan Visual Packaging Design terhadap Repurchase Intention Awl Cakes - Aulia Nur Utami; Isyana Rahayu (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the influence of brand experience and visual packaging design on consumers' repurchase intention for Awl Cakes products in Taraju District, Tasikmalaya Regency. Inconsistent sales fluctuations indicate a low level of repurchase intention among consumers, necessitating an in-depth investigation into the factors influencing it. This study employed a quantitative approach using an explanatory research design. Data were collected through questionnaires distributed to 100 respondents selected via purposive sampling, specifically consumers who had previously purchased Awl Cakes products, with the sample size determined using the Lemeshow formula. Data were analyzed using multiple linear regression with SPSS, preceded by instrument testing and classical assumption tests. The results indicate that the model demonstrates a good fit, with an R² value of 0.752, meaning that both independent variables explain 75.2% of the variation in repurchase intention. Brand experience has a positive and significant effect on repurchase intention (β = 0.478; t = 3.962; p = 0.000), as does visual packaging design (β = 0.410; t = 3.400; p = 0.001). These findings confirm that effective brand experience management and attractive packaging presentation are strategic factors in encouraging consumers to make repeat purchases, and can serve as a basis for developing more effective marketing strategies in the micro-enterprise segment.